For today and for the future: I was also involved with the project. When memory is present. - Orellana Román, Ximena Andrea (2021)
In this article, the exercise of memory construction of the present is systematized, as a practice of successful subjectivation promoted by the project “I was also there”, which focuses - since November 2019 - on the collection, registration, safeguarding and dissemination of stories of the rebellion that began in Chile in October 2019. This experience is promoted in light of the desire to recognize the diversity of voices of actors participating in demonstration and protest actions that go beyond the borders of the private sphere to occupy public space . The analytical exercise that is consigned has the purpose of giving an account of the process carried out, the mechanisms of operation and collaboration promoted by the project; the methods of analysis designed for the systematization of the information and, also, to propose some points of debate around the individual and collective subjectivation processes, in order to leave a trace in the memory and in the history of these experiences of struggle